Inappropriate Recognition of PPE - Dissanayake, D.M.N.P.; Karunarathne, W.V.A.D. (Department of Accountancy, University of Kelaniya, 2016)
LMN Company is a leading company which operates in the manufacturing industry. The company manufactures and sells aluminum extrusions. Sales of the company are carrying out by sales outlets and dealers, and also the company export the extrusions as well. The company manufactures extrusions in their own manufacturing plants, therefore the company possesses significant amount of non-current assets which are categorized in to various classes of assets. The company require huge amount of power to operate their machines. They can’t satisfy with the electricity supply which received from general electricity line. Therefore LMN Company has established a transformer in their factory premises after entering the agreement with Ceylon Electricity Board (CEB).